Hands-On Microservices with C# : Designing a Real-Worl, Enterprise-grade Microservice Ecosystem with the Efficiency of C# 7. - R. Cole, Matt (Packt Publishing Ltd, 2018)
In this book, we will show you how to report and reclaim memory, how to send and receive messages, and how to report and monitor the health of your entire microservice ecosystem. By the end of this book, you will be confident enough to develop a sturdy microservice architecture that works in a production setting--all by using the efficiency of C#.